Effect of oriented magnetic field on the solidified structure and soft magnetic properties of Fe78Si13B9 alloy - Chaochao Zeng; Yuhua Xu; Rongyu Liu; Hui Zhao; Zhenghou Zhu; Zhi Jia (Results in Physics, 2021)
In this paper, the growth of dendrites and its effect on soft magnetic properties of Fe78Si13B9 alloy during solidification under the effect of 0.18 T oriented magnetic field are studied. It shows that the magnetic field has strong guiding and promoting effect on the growth of dendrites. The primary branches of the α-Fe (Si) phase dendrites grow in parallel along the vertical direction of the magnetic field line, and the length of the primary branches reaches more than 1 mm. At the same time, the secondary branches of the α-Fe (Si) phase dendrites also follow the direction of the magnetic field line. It grows directional parallel to the direction of the magnetic field line, and connects the adjacent primary branches to form a grid-like magnetically guided solidification structure with uniform spacing; The soft magnetic properties of the magnetically guided solidified(MGSed) FeSiB alloy are much better than the non-magnetically guided solidified(NGSed) FeSiB alloy, and the maximum permeability (μm) of MGSed FeSiB alloy is as high as 964.4789, which is twice as much as that of NGSed alloys. MGSed alloys have better resistance to magnetic field saturation, and their saturated magnetic field Hj value reaches 12,000 Oe, which is more than 3 times that of NGSed alloys. This work provides a novel route for further development of FeSiB alloys with excellent soft magnetism.